PENERAPAN MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK - Ardella Angeliani; Totok Victor Didik Saputro (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study addresses the low mathematics learning outcomes observed among Grade III A students at SDN 09 Rangkang, where the class average was 55.48 and only 29.03% of students achieving the Minimum Completeness Criterion (KKM) of 70 during the pre-cycle assessment. This study aimed to improve these outcomes through the implementation of the Numbered Heads Together (NHT) cooperativelearning model. This research is a Classroom ActionResearch (CAR) conducted in two cycles, each consisting of three meetings with planning, implementation, observation, and reflection stages. The participant were 31 Grade III A students of SDN 09 Rangkang for the 2025/2026 academic year. Data were throught learning achievement tests, teacher and student activity observations, and documentation. The findings revealed significant improvement: the pre-cycle average of 55.48 increased to 61.61 in Cycle I with 45.16% completeness, and further increased to 81.45 in Cycle II with classical completeness of 90.32%, surpassing the established success indicator of 80%. These result indicate that the NHT cooperative learning model effectively enhances students mathematics learning outcomes.